Four families with immunodeficiency and chromosome abnormalities. Issue 7 (July 1979) - Candy, D C; Hayward, A R; Hughes, D T; Layward, L; Soothill, J F
Abstract : Six children, with severe deficiency of some or all of the immunoglobulins and minor somatic abnormalities, had chromosomal abnormalities: (1) 45, XY, t(13q/18q), (2) 46, XY, 21ps +, (3) two brothers 46, XY (inv. 7) (4) 45, X, t(11p/10p)/46X, iXq, t(11p/10p) and, (5) in addendum, 45, XX, -18;46, XX, r18. The chromosome abnormalities were detected in B- as well as T-lymphocytes (as evidenced by using both PHA- and PWM-stimulated cultures) in all probands, but one was mosaic in PHA culture, although all his PWM-stimulated cells were abnormal. Chromosomal variants were also detected in relatives of three and immunodeficiency in relatives of two.